OPTIMALISASI PENERAPAN OTOMASI SLIMS (SENAYAN LIBRARY MANAGEMENT SYSTEM) PADA RUANG BACA PENDIDIKAN ADMINISTRASI PERKANTORAN FKIP UNS - Ivan Wahyu Ramadhan; Tri Murwaningsih; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2019)
This research aimed to find out: (1) the optimization of SLiMS automation system in Reading Room of Office Administration Education Program Study of FKIP UNS (Teacher Training and Education Faculty of Sebelas Maret University), (2) the constraints encountered in applying automation system in Reading Room of Office Administration Education Program Study of FKIP UNS; and solution to the application of automation system in Reading Room of Office Administration Education Program Study of FKIP UNS in order to be more maximal. This study was a descriptive qualitative research. The sampling techniques employed were purposive and snow ball sampling ones. Data sources employed were informant, place, and event, as well as archive and document. Techniques of collecting data used were interview, observation, and documentation. Data validation was carried out using source and method triangulations. Technique of analyzing data used was an interactive model of analysis. The result of research showed that the application of SLiMS (Senayan Library Management System) automation in Reading Room of Office Administration Education Program Study of Teacher Training and Education Faculty of Surakarta Sebelas Maret University included: circulation service, retrieval system (OPAC), member administration, and literature processing. The constraints encountered in SLiMS application are administrator’s poor competency in using SLiMS automation system leading to less maximal system utilization, and inadequate facilities including the availability of one computer unit only, the limited number of reading table available, and the inadequate space condition. Availability of library materials is still lacking in terms of both quantity and content. The attempts taken to deal with such constraints were: to hold training activity for SLiMS automation system conducted by administrators of reading room, to repair and to provide facilities in reading room by proposing it to the central office through study program, for example, increasing the number of air conditioners (AC). In addition, he also asked for donations from alumnus to increase the collection of library materials.